Reactivity Assessment of Pozzolanic Materials for Partial Replacement of Cement in Concrete - (:unkn) unknown (My University, 2023)
Reductions in portland cement use have important benefits in reducing the embodied energy in concrete and controlling CO2 emissions. Developing new, sustainable, and low-carbon construction materials is critical in addressing climate change. Many industrial by-products are disposed of in landfills as waste materials. It is imperative to assess the pozzolanic reactivity of industrial by-products and other waste materials to develop alternative supplementary cementitious materials (SCMs) such as pozzolanic materials. This study evaluates the pozzolanic reactivity of seven different powdered materials: pottery cull, brick powder, lightweight aggregate fines, class C fly ash, silica fume, glass powder, and dolostone. Seven different pozzolanic reactivity test methods were employed: the Frattini test, strength activity index (SAI), ultrasound pulse velocity index, thermogravimetric analysis, calorimetry, electrical conductivity, and pH. A comparative study was performed to evaluate the efficiency and efficacy of various pozzolanic reactivity test methods through robust correlation analyses and a ranking method. The degree of pozzolanic reactivity of the tested materials was also compared. An analytical approach for calculating the amount of consumed portlandite is proposed for the electrical conductivity and pH test methods, and the results are then correlated with the Frattini and TGA results. Electrical conductivity and pH tests are rapid, effective, and direct methods for assessing pozzolanic reactivity. Finally, this study proposes an equation to predict the SAI of any potential pozzolan using its chemical and physical properties, thus providing more efficient and timely assessments.
Keywords: comparative analysis; Direct methods; Indirect methods; Pozzolanic reactivity; Supplementary cementitious materials; Sustainability